Infantile angioma. 2. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Spider nevus. This acquired form of angioma is very frequent, particularly during pregnancy and is not rare in children. The increased prevalence during pregnancy supported the role played by estrogens. This role is also supported by its frequency in liver diseases. However, estrogens cannot be the only causative factor. [...].